Synthesis of Penta- and Tetrasubstituted Quercetins and Their Fluorescent Properties - Kim, Yerim; Kim, Yongju (John Wiley & Sons Ltd., 2024)
Quercetin contains five hydroxy groups (OH) at positions 3, 5, 7, 3 ', and 4 '. The selective reaction of a hydroxy group in quercetin is an important strategy for the modulation of various properties of the derivatives. Herein, we report the synthesis of selective quercetin derivatives, wherein the oligoether chains were linked to the hydroxyl groups. Interestingly, the penta-substituted quercetin derivative exhibited a higher fluorescence intensity than the tetra-substituted one. The fluorescence behavior of synthetic derivatives was investigated using solvatochromism, molecular aggregations, computational calculations, and hydrogen bonds with solvents. The fluorescent penta-substituted quercetin derivative did not show any cytotoxicity up to 600 mu M concentration, showing a novel biocompatible fluorescent molecule. Here, we report the synthesis of penta- and tetra-substituted quercetin derivatives and their fluorescent properties. The derivatives were synthesized selectively by etherification in different ratios of acetone and water as solvents. Only molecule 1 emitted fluorescence in an aqueous solution. Furthermore, this quercetin derivative showed non-cytotoxicity with fluorescent imaging of cells. These results indicate that molecule 1 is a promising fluorescent dye.image